Case study: Coastal shipping in sub-Saharan Africa. Issue 4 (December 2022) - Konstantinus, Abisai; Woxenius, Johan
Highlights: Three coastal shipping lines in sub-Saharan Africa find business viable but demanding. They face a lack of demand, high port tariffs, poor port efficiency and customs. The Africa Continental Free Trade Area can mitigate the lack of intra-African trade. The COVID-19 pandemic severely affected maritime operations and the life of crews. Abstract: The development of coastal shipping (CS) in Africa has been identified as a way to bolster the continent's freight transport network. Thus, our study examined the recent CS experiences of three regional shipping lines in sub-Saharan Africa (SSA)—Ocean Africa Container Lines, Adom Mbroso Transport and United Africa Feeder Line—operating respectively in Southern, West and East Africa. We employed an in-depth case-study approach involving semi-structured interviews with senior managers, which enabled us to discover and understand the real-life phenomenon of successfully operating CS services in SSA today and how the COVID-19 pandemic has affected the three companies. Our study revealed gaps that need to be addressed in order to develop maritime transport in Africa's subregions, namely by clarifying the predicted appropriateness and credibility of different policies and which elements are more likely to generate positive behavioural change in regional shipping lines. It also revealed major barriers for CS, including customs, a lack of intra-regionally traded cargo and high tariffs and low efficiency at port. Although the establishment of the Africa Continental Free Trade Area and 2050 Africa's Integrated Maritime Strategy have clearly had positive effects, African states need to implement the policies in concert as well as improve the performance of ports. Last, concerning the pandemic, COVID-19-related restrictions have decreased transport demand for CS in SSA and limited crew changes, shore leaves and cargo operations. Although business viability has been negatively affected as a consequence, freight rates have increased across SSA and thus improved the sustainability of CS.